The Efficacy of the Management Programs of Columban College, Inc. - Bravo, Marlon F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study determined the efficacy of the Management Program of Columban College, Inc. It employed the descriptive method of research. The respondents of the study were the randomly selected 3rd to 4th-year students who were enrolled with major subjects and faculty members in the Management programs such as Bachelor of Science in Business Administration, Major in Management, Bachelor of Science in Tourism, and Bachelor of Science in Hotel and Restaurant Management for the academic year 2008-2009. The student’s perceived efficacy and teachers regarding Seminars got a descriptive rating of “Agree” and field trip obtained “Agree” both under co-curricular activities. The perception of the students and faculty members on the efficacy of the Management courses in terms of membership in the organizations has a descriptive rating of “Agree”; for the academic contests obtains “Moderately Agree”; and non-academic competitions garnered a descriptive rating of “Agree”. There is a significant difference Management programs’ perceived usefulness in relation to the non-academic contests, seminars, field trips, and membership in organizations. There is no significant difference in the perceived efficacy of the Management programs with regard to the academic competition, curriculum, laboratory, library, and facility.